Pomalidomide and dexamethasone grant rapid haematologic responses in patients with relapsed and refractory AL amyloidosis: a European retrospective series of 153 patients. (1st October 2020) - Milani, Paolo; Sharpley, Faye; Schönland, Stefan O.; Basset, Marco; Mahmood, Shameem; Nuvolone, Mario; Kimmich, Christoph; Foli, Andrea; Sachchithanantham, Sajitha; Merlini, Giampaolo; Wechalekar, Ashutosh; Palladini, Giovanni; et al.
Abstract: Pomalidomide demonstrated activity in the treatment of AL amyloidosis in three phase II clinical trials. We evaluated the safety and efficacy of 28-day cycles of pomalidomide and dexamethasone in 153 previously treated patients with systemic AL amyloidosis. Ninety-nine (65%) were refractory to the last line of therapy and 54 (35%) had relapsed. The median number of previous lines of therapy was 3 (range: 2–7): 143 patients (93%) previously received bortezomib, 124 (81%) lenalidomide, 114 (75%) oral melphalan, and 37 (24%) underwent autologous stem cell transplant. At the completion of cycle 6, 68 (44%) patients obtained at least partial haematologic response, with 5 complete responses (CR, 3%), 35 very good partial responses (VGPR, 23%). Haematologic response resulted in improved overall survival (median survival 50 vs. 27 months, p  = .033) in a 6 months landmark analysis. Obtaining at least partial response was also associated with a significant improvement of the progression-free survival (median PFS 37 vs. 18 months, p  < .001). Pomalidomide is an effective treatment for heavily pre-treated patients with AL amyloidosis. Haematologic responses are associated with an overall survival advantage.